2021
DOI: 10.3389/fnins.2021.733984
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Signatures in the Food Finding Test in Mice With Normal and Alzheimer’s Disease-Pathological Aging With Special Concerns on the Effects of Social Isolation

Abstract: The temporal course and the severity of the involution of sensory systems through aging can be critical since they ensure the ability to perceive and recognize the world. In older people, sensory impairments significantly increase their risk of biological, psychological, and social impoverishment. Besides this, olfactory loss is considered an early biomarker in Alzheimer’s disease (AD) neurodegenerative process. Here we studied olfactory ethograms in middle-aged male and female gold-standard C57BL/6 mice and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…Thus, like in humans ( Gerst-Emerson and Jayawardhana, 2015 ), housing/social conditions can significantly impact animal behavior, morbidity, and mortality outcomes. However, only a few laboratories have studied the effects of poor social housing in AD models, despite reporting worsened cognition and neuropathology ( Pietropaolo et al, 2009 ; Huang et al, 2015 ; Muntsant and Giménez-Llort, 2020 ; Peterman et al, 2020 ), enhancement of olfactory patterns ( Marín-Pardo and Giménez-Llort, 2021 ), body and organs weight loss, and increased asymmetric atrophy of the hippocampus ( Muntsant and Giménez-Llort, 2020 ). Interestingly, the present work shows that even short isolation could increase the activity in 3xTg-AD mice and counteract the low activity levels associated with the AD-genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, like in humans ( Gerst-Emerson and Jayawardhana, 2015 ), housing/social conditions can significantly impact animal behavior, morbidity, and mortality outcomes. However, only a few laboratories have studied the effects of poor social housing in AD models, despite reporting worsened cognition and neuropathology ( Pietropaolo et al, 2009 ; Huang et al, 2015 ; Muntsant and Giménez-Llort, 2020 ; Peterman et al, 2020 ), enhancement of olfactory patterns ( Marín-Pardo and Giménez-Llort, 2021 ), body and organs weight loss, and increased asymmetric atrophy of the hippocampus ( Muntsant and Giménez-Llort, 2020 ). Interestingly, the present work shows that even short isolation could increase the activity in 3xTg-AD mice and counteract the low activity levels associated with the AD-genotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, sixmonth-old 3xTg-AD mice did not show olfactory deficit to social and non-social (almond and banana) odors [37]. The outcome of experiments evaluating olfaction by finding buried food [35,38] can be deeply confounded by metabolic/motivational processes, known to be altered in the 3xTg-AD mice [39]. In another case, sex-related olfactory function was measured, which can be influenced by sexual drive [36].…”
Section: Discussionmentioning
confidence: 99%
“… 37 , 50 Thus, our results further suggested more vascular network is to be mature and engaged in blood circulation after 8‐weeks EAST36 treatment. Considering that olfactory dysfunction and neuropsychiatric symptoms mutually interact with AD progression and precede the vast neurodegeneration in the brain, 27 , 51 , 52 , 53 treatment of olfactory dysfunction and neuropsychiatric symptoms is not only the issue of life quality improvement for the patient but also the intervention of AD progression. Excitedly, our data suggested that EAST36 treatment worked in this position by relieving early neurological symptoms and Aβ accumulation in cerebral vessels in AD mice, greatly downregulating the risks of progressive cognitive decline in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Food‐finding test, 27 elevated‐plus maze (EPM), 28 and Morris‐water maze test 29 were applied to assess the olfactory symptoms, anxiety‐like symptoms, and cognitive deficit in mice, respectively. The detailed performance was described in the Appendix S1 .…”
Section: Methodsmentioning
confidence: 99%